A Complex of Prehistoric Fortifications in the Moldavian Subcarpathians (Eastern Romania). Contributions to the Understanding of the Middle Bronze Age - Diaconu, Vasile; Gerea, Alexandra; Tătaru, Dragoș; Năstase, Eduard; Cerbu, Bogdan; Sava, Gabriela; Gâză, Oana; Ilie, Maria (Analecta Archaeologica Ressoviensia, 2026)
This paper discusses three recently discovered fortified sites located in the Subcarpathian area of eastern Romania, investigated through LiDAR scanning and intrusive archaeological research. Chronologically, the fortifications analysed in this study date to the Middle Bronze Age and are attributed to the Costișa culture. The sites are situated in close proximity to one another and may have formed part of a wider defensive system marking the territorial limits of this cultural environment. At the same time, they appear to have held strategic local importance by controlling access routes to areas rich in salt resources. Excavations conducted at one of the sites provided absolute chronological data ranging between 2143–1531 cal BC, correlating well with previously obtained radiocarbon dates for the Costișa culture.